Anti-diabetic potential of apigenin, luteolin, and baicalein via partially activating PI3K/Akt/Glut-4 signaling pathways in insulin-resistant HepG2 cells - Lingchao Miao; Haolin Zhang; Meng Sam Cheong; Ruting Zhong; Paula Garcia-Oliveira; Miguel A. Prieto; Ka-Wing Cheng; Mingfu Wang; Hui Cao; Shaoping Nie; Jesus Simal-Gandara; Wai San Cheang; et al. (Food Science and Human Wellness)
Dietary flavonoids are abundant in natural plants and possess multiple pharmacological and nutritional activities. In this study, apigenin, luteolin, and baicalein were chosen to evaluate their anti-diabetic effect in high-glucose and dexamethasone induced insulin-resistant (IR) HepG2 cells. All flavonoids improves the glucose consumption and glycogen synthesis abilities in IR-HepG2 cells via activating glucose transporter protein 4 (GLUT4) and phosphor-glycogen synthase kinase (GSK-3β). These flavonoids significantly inhibited the production of reactive oxygen species (ROS) and advanced glycation end-products (AGEs), which were closely related to the suppression of the phosphorylation form of NF-κB and P65. The expression levels of insulin receptor substrate-1 (IRS-1), insulin receptor substrate-2 (IRS-2) and phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt) pathway in IR-HepG2 cells were all partially activated by the flavonoids, with variable effects. Furthermore, the intracellular metabolic conditions of the flavonoids were also evaluated.